2010
DOI: 10.1007/s12230-010-9150-7
|View full text |Cite
|
Sign up to set email alerts
|

Cooking Methods and Storage Treatments of Potato: Effects on Carotenoids, Antioxidant Activity, and Phenolics

Abstract: The influence of genotype, cooking method, and storage treatments on potato compounds associated with improved human health was analyzed. Antioxidant activity (AA), total phenolics (TP), and total carotenoids (xanthophyll carotenoids, CAR) were determined in eight genotypes using 2,2-diphenyl-1-picrylhydrazyl (DPPH), Folin-Ciocalteu reagent, and spectrophotometric absorbance, respectively. Individual phenolic and carotenoid composition was analyzed using high performance liquid chromatography (HPLC) in three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
101
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 67 publications
24
101
2
1
Order By: Relevance
“…Several authors have described a considerable reduction in the amount of TPC during cooking, depending on the cultivar and cooking methods (Blessington et al, 2010;Perla et al, 2012). We observed that the changes in the TPC of the potato flesh were more dependent on the genotype of each cultivar (Table 3).…”
Section: Y Yang Et Al / Food Chemistry XXX (2015) Xxx-xxxmentioning
confidence: 60%
See 1 more Smart Citation
“…Several authors have described a considerable reduction in the amount of TPC during cooking, depending on the cultivar and cooking methods (Blessington et al, 2010;Perla et al, 2012). We observed that the changes in the TPC of the potato flesh were more dependent on the genotype of each cultivar (Table 3).…”
Section: Y Yang Et Al / Food Chemistry XXX (2015) Xxx-xxxmentioning
confidence: 60%
“…Although the phenolic content has been extensively studied for raw potatoes (Rumbaoa, Cornago, & Geronimo, 2009;Stushnoff et al, 2008), there have been many discrepancies regarding the effect of heat treatments on the phenolics and antioxidant activity of potato samples, which could be due to the different processing conditions. Some literature has suggested that a shorter cooking time and lower temperature increased or did not change the total phenolic content and the antioxidant capacity (Blessington et al, 2010;Lachman et al, 2013;Mulinacci et al, 2008;Navarre, Shakya, Holden, & Kumar, 2010;Perla, Holm, & Jayanty, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Following 9 months storage at 4°C the levels of zeaxanthin and antheraxanthin decreased, whereas the level of lutein increased; overall, however, there was only a small decrease in total carotenoid content. In non-stored potato tubers and in three storage conditions all storage treatments were higher in carotenoid content (expressed as lutein) in four cultivars and the interaction between genotype was significant for carotenoid content (Blessington et al 2010).…”
mentioning
confidence: 89%
“…Carotenoid content was observed to be lower in boiled as compared to raw potatoes, however, no significant difference in other methods of cooking was observed (Blessington et al 2010). Isomerisation and oxidation reactions upon heating of carotenoids may cause small losses, which were later confirmed by Rautenbach et al (2010) when they observed an average decrease of 9.7% in boiling sweetpotato for 12 min.…”
mentioning
confidence: 89%
See 1 more Smart Citation